Gender and Business Ethics of Enterprise Students and Nascent Entrepreneurs Engaged in Entrepreneurship Education. (September 2015) - Lourenço, Fernando; Sappleton, Natalie; Cheng, Ranis
It has generally been argued that women have higher moral standards or display greater concern about the effects of their actions on others when responding to ethical dilemmas. However, the findings of empiricists have hardly been conclusive. We contend that it is important to investigate the ethical attitudes towards business practice of those who are at the early phase of the entrepreneurship path such as enterprise students ( n = 128) and nascent entrepreneurs ( n = 204). The findings revealed sex differences in the ethical attitudes of enterprise students, but not of nascent entrepreneurs. In addition, the business ethics of male nascent entrepreneurs were significantly higher than those of male enterprise students. We argue that sex-role socialisation reduces differences among individuals performing similar activities, and use moral development theory to explain that ethical values evolve over time.